Northwest Coast Ceremonialism: The Works of J.A. Jacobsen (1853-1947) - Aaron Glass (European Journal of American Studies, 2014)
Johan Adrian Jacobsen (1853-1947), a Norwegian sailor, spent much of the 1880s collecting ethnographic specimens for traveling shows and museums. His most well known collections were from the Arctic and Northwest Coast of North America. In an attempt to publicize his adventures and legitimize his collections for scholars and curators, he wrote a few articles in German about the people he had visited, especially the so-called secret societies among the Nuxalk [Bella Coola] and Kwakwaka’wakw [Kwakiutl]. Although somewhat amateurish, these reports represent a transition in genre between travel accounts and professional ethnography, and are valuable for informing our understanding of early Northwest Coast anthropology. The translation of the works of Jacobsen from the original German was done by Richard Bland (University of Oregon). The original illustrations mentioned in the introduction could not be reproduced here.